2019
DOI: 10.1177/1078087419835968
|View full text |Cite
|
Sign up to set email alerts
|

Social and Environmental Justice in Waterfront Redevelopment: The Anacostia River, Washington, D.C.

Abstract: Waterfront redevelopment projects have often been criticized for prioritizing attractive skylines and glittering facades over the needs of local communities. Recently, however, they have increasingly seen goals of social and environmental justice integrated into their vision statements. This article focuses on the redevelopment of the Anacostia River in Washington, D.C. Since the early 2000s, the formerly neglected and contaminated river has been at the center of extensive regeneration efforts through the Anac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 60 publications
0
19
0
1
Order By: Relevance
“…For example, in a recent study comparing the use of greening in Berlin (Germany) and Detroit (United States), the authors found examples of green spaces that served as curative bridges with explicit recognition of historical racial violence embedded in them. Another case is the planned 11th street bridge park in Washington DC, which, despite staying shy of returning land to displaced black residents, aims at allowing local control over development in the neighborhood through a linked land trust (Avni and Fischler, 2019).…”
Section: From Historical Diagnostic To Social-ecological Justicementioning
confidence: 99%
“…For example, in a recent study comparing the use of greening in Berlin (Germany) and Detroit (United States), the authors found examples of green spaces that served as curative bridges with explicit recognition of historical racial violence embedded in them. Another case is the planned 11th street bridge park in Washington DC, which, despite staying shy of returning land to displaced black residents, aims at allowing local control over development in the neighborhood through a linked land trust (Avni and Fischler, 2019).…”
Section: From Historical Diagnostic To Social-ecological Justicementioning
confidence: 99%
“…While critical scholars have documented these transformations for several decades, only recently have they begun to apply more extensively explicit concepts of justice and equity in their investigation of urban waterfronts (Wessells 2014). Increasingly, waterfronts have been engaged with from the perspectives of both social and environmental justice, but the two terms have rarely been discussed in integration (Avni and Fischler 2019). The lens of environmental justice is important to the analysis of waterfronts since as former industrial zones (and in some cases, current industrial zones), they have suffered from contamination, pollution, and overall neglect.…”
Section: Conflicts Of Social and Environmental Justicementioning
confidence: 99%
“…In particular, the growing scholarly engagement with sustainability and green gentrification in the last two decades has helped to unpack the social impacts of substantial greening interventions such as waterfront parks, especially when they are executed in proximity to marginalized communities (Bryson 2013; Curran and Hamilton 2017; Gould and Lewis 2017; Anguelovski et al 2018). A social justice lens is equally important to critically evaluate who has a voice in the process, who benefits and who loses from revitalization, and whether it promotes equity or, alternatively, perpetuates injustice (Avni and Fischler, 2019).…”
Section: Conflicts Of Social and Environmental Justicementioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, there has been a renewed interest in equity planning and social justice (Fincher and Iveson 2012;Marcuse et al 2009;Avni and Fischler 2019;Zapata and Bates 2015). once again appeared as central issues in planning theory (Reece 2018;Lake 2017).…”
Section: Just Urban Governancementioning
confidence: 99%